Time Lapse Seismicity Study of the Sub Sahara West Africa and the Gulf of Guinea Region - Ayodeji Adekunle Eluyemi; Awosika Damilola Doctor; Adebisi Oluwakemi Deborah; Saurabh Baruah (Research Developments in Science and Technology Vol. 1, 2022)
Time lapse seismicity map of the gulf of guinea and sub-Sahara west African region from the period of 1918 up to 2017, covering a total period of ninety-nine years gave an in depth knowledge of seismic activities in the study region. This is with the utmost intention to examining the distribution of seismicity in the region with respect to time and enabling us to critically understand the seismogenic zones, with the view to forecast into the future the earthquake hazard of the region. The available seismicity data were divided into five (5) seismic windows: 1918-1937; 1938-1957, 1958-1977; 1978-1997 and 1998-2017. We inferred that there has been an increase in seismicity since the time period of 1958 up till date. The increase in the number of recorded seismicity could be as a result of either an increase in the number of the installed seismometers with the capability of detecting both small and big magnitude events or the region is approaching active phase of seismicity. The intraplate seismicity experienced in the region was as a result of transmission of a seismic waves from the mid Atlantic ridge (plate boundaries separating the African from the South America). An insight from the depth section plots of the selected fault plane solutions (FPS) of the four identified major fractured zones investigated in Eluyemi et al. (2019), presented the depth distributions of the FPS, projected depth view and nodal plane projection, that reveals a shallow seismogenic source of events in the study region. However, the orientation of the pressure and tensional axes help us to understand the geometrical and mechanical classification and assumed direction of the stress field of the region.